Hakim–Adams Syndrome: An Unusual Cause of Reversible Postoperative Coma - Saleh, Mohamed; Bouex, Marine (Frontiers in Medicine, 2016)
We report the case of a 72 years old patient presenting in our ICU with persistent postoperative coma in a context of recent unexplored neurological dysfunction. Detailed medical history taking from the patient’s family revealed he recently suffered from gait instability, urinary incontinence and slight cognitive impairment. These constituted the clinical triad of normal pressure hydrocephalus syndrome. The presence of normal cerebrospinal fluid pressure and distinctive radiological findings confirmed the diagnosis of normal pressure hydrocephalus or Hakims-Adams syndrome. After cerebrospinal fluid volume soustraction, the patient recovered a normal level of consciousness and was successfully weaned from mechanical ventilation. Normal pressure hydrocephalus should be included in the differential diagnosis of delayed postoperative arousal, especially in the elderly.